Plasma manganese and selenium levels in paediatric chronic kidney disease patients measured by high resolution sector field inductively coupled plasma mass spectrometry - Verma, Subhrata (2023)
Manganese (Mn) and Selenium (Se) deficiencies are noted in adult patients with chronic kidney disease (CKD). However, levels of these trace elements have not been well studied in the paediatric CKD population. We determined the Mn and Se levels in a single-institution cohort of paediatric patients with CKD.